2023
DOI: 10.3390/biom13050804
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Synoeca-MP Antimicrobial Peptide with IDR-1018 Stimulates Proliferation, Migration, and the Expression of Pro-Regenerative Genes in Both Human Skin Cell Cultures and 3D Skin Equivalents

Abstract: In skin lesions, the development of microbial infection affects the healing process, increasing morbidity and mortality rates in patients with severe burns, diabetic foot, and other types of skin injuries. Synoeca-MP is an antimicrobial peptide (AMP) that exhibits activity against several bacteria of clinical importance, but its cytotoxicity can represent a problem for its positioning as an effective antimicrobial compound. In contrast, the immunomodulatory peptide IDR-1018 presents low toxicity and a wide reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In this sense, it has also been observed that some antimicrobial peptides, such as the synthetic A-hBD-2 or the LL-37 peptide (the only member of the human cathelicidin family), have the ability to facilitate the wound healing process by stimulating cell migration in both skin cells and mesenchymal stem cells [14,22]. Likewise, Synoeca-MP, an AMP with a broad antimicrobial spectrum, has also been shown to be useful in skin repair when combined with host-defense peptides IDR-1018 [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it has also been observed that some antimicrobial peptides, such as the synthetic A-hBD-2 or the LL-37 peptide (the only member of the human cathelicidin family), have the ability to facilitate the wound healing process by stimulating cell migration in both skin cells and mesenchymal stem cells [14,22]. Likewise, Synoeca-MP, an AMP with a broad antimicrobial spectrum, has also been shown to be useful in skin repair when combined with host-defense peptides IDR-1018 [23].…”
Section: Discussionmentioning
confidence: 99%
“…The proregenerative potential of various AMPs is associated with their ability to modulate the inflammation process, which is key in the restoration of normal tissue architecture during wound repair [36]. Peptides such as IDR-1018, which exert their action through regulation of the inflammatory response, can induce the repair of skin wounds [13,23,37]. It has been observed that both Clavanin A and Mastoparan-MO are capable of modulating innate immunity by stimulating leukocyte recruitment to the site of infection and production of immune mediators GM-CSF, IFN-γ, and MCP-1 while suppressing excessive inflammatory response by increasing the synthesis of anti-inflammatory cytokines such as IL-10 and repressing the levels of proinflammatory cytokines IL-6, IL-12, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…These models incorporate multiple cell types and layers, including keratinocytes, fibroblasts, and sometimes immune cells, closely recapitulating the microenvironment of a healing wound. The inclusion of ECM components in these models enhances their physiological relevance, making them valuable tools for studying aspects such as tissue regeneration and re-epithelialization [47,48].…”
Section: Three-dimensional Skin Equivalentsmentioning
confidence: 99%
“…The combination of cecropin D-derived peptide and caspofungin showed the synergistic effects against Candida albicans ( Guevara-Lora et al ). The study of Alencar-Silva et al ( 2023 ) demonstrated the decreased cytotoxicity of Synoeca MP through its combination with IDR-1018. The combination also enhanced cell proliferation and migration and accelerated wound re-epithelialization, which opens the possibility for the development of new strategies in treatment of skin injuries (Alencar-Silva et al, 2023 ).…”
Section: Randd Directions Of Ampsmentioning
confidence: 99%